Políticas públicas de juventude e meio ambiente: o que a percepção socioambiental dos jovens pode dizer? - Tarcísio Augusto Alves Silva (Universidade do Vale do Rio dos Sinos (UNISINOS), 2016)
Some authors (Krischke, 2000; Carvalho, 2004) have drawn attention to the fact that the environmental struggle has been an important field for the establishment of a new political culture among young people. Similarly, the various studies that have been com-missioned mainly by companies and the Third Sector in order to understand the profile of the young Brazilian population have identified an interest of this social group in the environment. Following this same movement, government actions have, although incipi-ently sought to include efforts to implement an environmental agenda in which young people are protagonists. In this sense, the present proposal aims to reflect on the social and environmental problems identified by high school students in some of the 12 Per-nambuco development regions and, at the same time, to discuss how the environmental awareness of young people can contribute to the establishment of public policies for them.